Cross-Border Portfolio Diversification under Trade Linkages - Makram Khalil (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This study uncovers a cross-border financial diversification motive related to goods and services trade. Using the IMF CPIS panel data set for a broad set of country pairs and for the period 2001-2012, I find empirical evidence that the share of equity in a bilateral portfolio decreases with bilateral trade. The driving force behind this pattern are holdings of foreign debt, i.e. increasing trade intensity is strongly related to increasing holdings of foreign debt and less so to holdings of foreign equity. The empirical findings are in line with the predictions of a calibrated two-country two-goods portfolio choice model where in equilibrium equity is used to hedge against supply shocks and real bonds are used to hedge against a global preference shock. For reasonable parameter values, strengthening trade linkages induce the risk-averse representative agent to adjust her portfolio of foreign assets away from foreign equity and towards foreign bonds. The findings of this study imply that bilateral trade provides an explanation for why cross-border portfolio investments are sometimes dominated by equity investments and sometimes dominated by debt investments. This matters since both asset classes are means of risk-sharing but differ with respect to their effects on macroeconomic outcomes and financial stability.
Keywords: F21; F36; G11; 330